Perceived discrimination, critical consciousness, and health in African-American women with HIV - Kelso, Gwendolyn A. (2014)
Thesis (Ph.D.)--Boston UniversityPerceived racial discrimination (PRD), perceived gender discrimination (PGD), and discrimination-related stress (DS) have been shown to predict poor health and substance abuse in African-American women. They may contribute to racial disparities in both HIV infection and incarceration, which disproportionately affect African-American women. Critical consciousness (CC), the awareness of sociopolitical inequality, may provide a buffer against the effects of discrimination on health outcomes. This study examined (1) the effects of PGD, PRD, and DS on health and substance use and of CC as a moderator of these relationships in HIV-infected African-American women; and (2) the relationships of PRD, PGD, DS, and CC to HIV status and incarceration in HIV-infected and uninfected women. Seventy-three HIV-infected and 25 HIV-uninfected African-American women (ages 26 to 72 years) from the Chicago site of the Women's Interagency HIV Study completed self-report measures of PGD, PRD, DS, CC, depressive symptoms, quality oflife, cigarette smoking, anti-retroviral medication adherence and substance use. Blood pressure, body mass index, cholesterol, CD4+ cell count, and HIV viral load were also measured. Multiple linear and logistic regressions revealed that in HIV-infected women, PRD significantly related to higher and PGD related to lower blood pressure, likelihood of cigarette smoking, and likelihood of crack/cocaine/heroin and marijuana use. PRD significantly related to lower viral load when controlling for DS. Path analyses showed a significant direct relation of PRD to lower depressive symptoms, but a significant indirect relation to higher depressive symptoms as mediated by DS. Critical consciousness was found to relate to better HIV health markers in the context of high discrimination. At higher PGD, PRD, and DS, women with higher CC had higher CD4+ counts and lower viral load than women with lower CC. Partial correlations showed that in HIV-infected and uninfected women, there were significant positive relations of incarceration to PGD, PRD, DS, and CC. These results suggest that relationships of PGD, PRD and DS with health and substance use are complex, being protective for some outcomes but conferring risk for others. CC related to better health outcomes and provided a buffer against poor HIV health at high levels of discrimination